2012
DOI: 10.1124/jpet.112.200519
|View full text |Cite
|
Sign up to set email alerts
|

5-Benzylglycinyl-Amiloride Kills Proliferating and Nonproliferating Malignant Glioma Cells through Caspase-Independent Necroptosis Mediated by Apoptosis-Inducing Factor

Abstract: 59-Βenzylglycinyl-amiloride (UCD38B) and glycinyl-amiloride (UCD74A) are cell-permeant and cell-impermeant derivatives of amiloride, respectively, and used here to identify the cellular mechanisms of action underlying their antiglioma effects. UCD38B comparably kills proliferating and nonproliferating gliomas cells when cell cycle progression is arrested either by cyclin D1 siRNA or by acidification. Cell impermeant UCD74A inhibits plasmalemmal urokinase plasminogen activator (uPA) and the type 1 sodium-proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…AIF-mediated glioma necrosis produced by UCD38B is independent of canonical apoptosis Pasupuleti et al, 2013) and appears to be distinct from ripoptosomemediated necroptosis (Feoktistova et al, 2012). RIP-1 inhibition by necrostatin does not alter the anticancer cytotoxicity of UCD38B .…”
Section: Ucd38b Alters Endosomal Trafficking In Gliomasmentioning
confidence: 92%
See 4 more Smart Citations
“…AIF-mediated glioma necrosis produced by UCD38B is independent of canonical apoptosis Pasupuleti et al, 2013) and appears to be distinct from ripoptosomemediated necroptosis (Feoktistova et al, 2012). RIP-1 inhibition by necrostatin does not alter the anticancer cytotoxicity of UCD38B .…”
Section: Ucd38b Alters Endosomal Trafficking In Gliomasmentioning
confidence: 92%
“…types Pasupuleti et al, 2013). Previously, we demonstrated that UCD38B is a cell-permeant molecule that rapidly initiates a set of intracellular events causing mitochondrial depolarization with the release and nuclear translocation of AIF.…”
Section: Ucd38b Alters Endosomal Trafficking In Gliomasmentioning
confidence: 99%
See 3 more Smart Citations